2017
DOI: 10.1371/journal.ppat.1006141
|View full text |Cite
|
Sign up to set email alerts
|

An HSV-2 Trivalent Vaccine Is Immunogenic in Rhesus Macaques and Highly Efficacious in Guinea Pigs

Abstract: A genital herpes vaccine is urgently needed to prevent pain and suffering, reduce the incidence of neonatal herpes, and decrease the risk of HIV acquisition and transmission that accompanies genital infection. We evaluated a trivalent HSV-2 subunit antigen vaccine administered with CpG and alum in rhesus macaques and guinea pigs. The vaccine contains glycoproteins C, D and E (gC2, gD2, gE2) to block virus entry by gD2 and immune evasion by gC2 and gE2. In rhesus macaques, the trivalent vaccine induced plasma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 50 publications
2
79
0
1
Order By: Relevance
“…However, the risk of using live vaccines in pregnancy is likely to be unacceptable at the regulatory level. It might be fruitful, therefore, to reconsider the use of polyvalent subunit, inactivated, or disabled infectious single-cycle (DISC) virus preparations in at-risk women for the protection of their babies from neonatal HSV ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of using live vaccines in pregnancy is likely to be unacceptable at the regulatory level. It might be fruitful, therefore, to reconsider the use of polyvalent subunit, inactivated, or disabled infectious single-cycle (DISC) virus preparations in at-risk women for the protection of their babies from neonatal HSV ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“… 67 Given that the gD/AS04 subunit vaccine demonstrated no efficacy against HSV-2 in the Phase 3 field study 68 a variety of vaccines employing multiple antigenic targets (gC, gD, gE in combination) have been tested and have met with success in animal models of HSV pathogenesis. 69 71 Furthermore, Genocea Biosciences tested the GEN-003 vaccine containing both soluble gD and the ICP4.2 T-cell epitope in phase 2 trials, resulting in a measurable reduction in viral shedding (though comparable to valacyclovir drug therapy). 72 …”
Section: Neutralizing Vs Non-neutralizing Antibody Responsesmentioning
confidence: 99%
“…Nevertheless, there have been some positive clinical achievements. For example, in a recent preclinical study, an HSV2 trivalent subunit vaccine containing glycoproteins C, D, and E (gC2, gD2, and gE2) showed immunogenicity in rhesus macaques and displayed more than 97% efficacy in guinea pigs . Also, results from a phase III clinical trial study showed that a recombinant glycoprotein D vaccine, conferred approximately 74% prevention of genital HSV disease in women seronegative for both HSV serotypes …”
Section: Introductionmentioning
confidence: 99%